دورعملیات ادارة المعرفة في البراعة الاستراتيجية : دراسة تحليلية لآراء عينة من أعضاء مجالس الكليات في عدد من الجامعات الخاصه في مدينة أربيل - Tofiq, Kaywan S. (Polytechnic Journal of Humanities and Social Sciences, 2024)
The research seeks to identify the content of knowledge management processes and the extent of their contribution to achieving the goals of organizations, especially regarding strategic ingenuity. Effect between the variables of the study and developed a set of sub-hypotheses for this and for the purpose of testing a questionnaire design for that and analysis using the spss system has been used and the research has reached a set of conclusions, the most important of which is the existence of a strong correlation and strong influence between the main and secondary variables at the public and private levels. The research suggested a set of recommendations in the light of the conclusions, including the need to harness the strong relationships between the variables and direct them towards the private universities in Erbil under study, with the need to document the relationship between each dimension of knowledge management operations and strategic prowess. Keywords: knowledge management operations, strategic dexterity, private universities in the city of Erbil.